2012
DOI: 10.1143/apex.5.082105
|View full text |Cite
|
Sign up to set email alerts
|

Cyan Superluminescent Light-Emitting Diode Based on InGaN Quantum Wells

Abstract: An InGaN superluminescent light-emitting diode (SLED) with emission as long as 500 nm is presented. Up to now, an SLED with such a long wavelength was hindered, because the gain of indium-rich layers was not sufficient for operating in superluminescence mode. We used an epitaxial structure with high material gain as well as a special chip design of curved waveguide to solve this problem. The SLED reached an output power of >4 mW with a spectral bandwidth of 4.4 nm driven in pulsed mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Table 1 summarizes the design and performance of the demonstrated GaN-based SLDs, comparing the emission wavelength, substrate material, configuration, waveguide design, and the maximum light output power reported in each case. 405 nm c-GaN "j-shape" waveguide curved ridge 350 mW (cw) [24] 408 nm c-GaN "j-shape" waveguide "j-shape" ridge 200 mW (cw) [25] 410 ~ 445 nm c-GaN tilted waveguide 2 µm ridge 30 ~ 55 mW (cw) [26] 420 nm c-GaN tilted facet 2 µm ridge 2 mW (cw) 100 mW (pulse) [27] 420 nm c-GaN "j-shape" waveguide AR/HR coating 3 µm ridge 200 mW (cw) [28] 439 nm m-GaN facet roughening 4 µm ridge 5 mW (pulse) [29] 443 nm c-GaN curved waveguide 2 µm ridge 100 mW (cw) [30] 445 nm c-GaN oblique facet 5 µm ridge - [31] 447 nm Semipolar GaN passive absorber 7.5 µm ridge 256 mW (cw) [17] 500 nm c-GaN curved waveguide 2 µm ridge 4 mW (pulse) [32] Since most of InGaN/GaN QW SLDs are grown on a polar, c-plane GaN substrate, there is a growing interest to develop high efficient violet-blue SLDs on nonpolar or semipolar substrates owing to a reduced polarization field presented in the QW structure [2]. Studies on semipolar and nonpolar GaN-based LEDs and LDs have revealed that the enhanced electron and hole wavefunction overlap is expected for InGaN/GaN QWs grown on nonpolar (m-plane) and semipolar GaN substrates, leading to an enhanced internal quantum efficiency [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the design and performance of the demonstrated GaN-based SLDs, comparing the emission wavelength, substrate material, configuration, waveguide design, and the maximum light output power reported in each case. 405 nm c-GaN "j-shape" waveguide curved ridge 350 mW (cw) [24] 408 nm c-GaN "j-shape" waveguide "j-shape" ridge 200 mW (cw) [25] 410 ~ 445 nm c-GaN tilted waveguide 2 µm ridge 30 ~ 55 mW (cw) [26] 420 nm c-GaN tilted facet 2 µm ridge 2 mW (cw) 100 mW (pulse) [27] 420 nm c-GaN "j-shape" waveguide AR/HR coating 3 µm ridge 200 mW (cw) [28] 439 nm m-GaN facet roughening 4 µm ridge 5 mW (pulse) [29] 443 nm c-GaN curved waveguide 2 µm ridge 100 mW (cw) [30] 445 nm c-GaN oblique facet 5 µm ridge - [31] 447 nm Semipolar GaN passive absorber 7.5 µm ridge 256 mW (cw) [17] 500 nm c-GaN curved waveguide 2 µm ridge 4 mW (pulse) [32] Since most of InGaN/GaN QW SLDs are grown on a polar, c-plane GaN substrate, there is a growing interest to develop high efficient violet-blue SLDs on nonpolar or semipolar substrates owing to a reduced polarization field presented in the QW structure [2]. Studies on semipolar and nonpolar GaN-based LEDs and LDs have revealed that the enhanced electron and hole wavefunction overlap is expected for InGaN/GaN QWs grown on nonpolar (m-plane) and semipolar GaN substrates, leading to an enhanced internal quantum efficiency [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Gan based blue light emitting diodes (LEDs) have attracted considerable interest in the development of optoelectronic devices [1,2]. Especially, InGaN/GaN multiple quantum well (MQW) are being used as the active layers for optical devices such as light-emitting diodes (LEDs) and laser diodes (LDs).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the laser‐like beam characteristics allow efficient coupling to fiber optics. Continuous improvements have stretched the spectral range where SLEDs are available across near infra‐red (IR), red, blue, and recently green . Consequently, possible applications might be expanded from optical coherence tomography, fiber‐optic gyroscopes to next‐level visualization technologies such as either high‐power pico‐projectors or low‐power near to eye light sources required for virtual and augmented reality .…”
mentioning
confidence: 99%
“…Therefore, it is required to reduce the facet reflectivity and to avoid the back coupling of residually reflected modes into the waveguide. This is achieved by applying, e.g., high‐quality anti‐reflection coatings (ARCs), bent or tapered waveguides, tilted facets, or mode deflectors at the end of the waveguide . However, except for ARCs, most of these methods suppress feedback by introducing additional absorption or deflection of light out of the waveguide, which likewise result in reduced efficiencies.…”
mentioning
confidence: 99%
See 1 more Smart Citation